Notice of Supposed Cranium of Robert Logan of Restalrig - Robertson, David H (Proceedings of the Society of Antiquaries of Scotland, 1864)
A skull and some associated bones were unearthed from beneath St Mary’s Church in Leith in the 1840s. The author, having examined these bones and the history of the church, suggests that they may belong to Robert Logan of Restalrig, who was buried and later disinterred when he was suspected of treason. However, David Laing disagrees with this argument, as he believes there is no solid evidence linking the bones to Logan.